A life cycle assessment of biodiesel from waste cooking oil using bifunctional magnetic nanocatalyst - Srikumar, Kashleta; Tan, Yie Hua; Rashid, Umer; Tan, Inn Shi; Kansedo, Jibrail; Mubarak, Nabisab Mujawar; Yek, Peter Nai Yuh; Chai, Pui Vun; Karri, Rama Rao; Chan, Yen San (Elsevier, 2025)
In recent decades, excessive fossil fuel consumption, driven by rising global energy demand and population growth, has led to health risks, energy shortages, and environmental concerns. Consequently, there is a growing shift towards biodiesel as a renewable alternative, emphasizing the need for cost-effective, sustainable feedstock, and efficient catalysts. This life cycle assessment (LCA) study investigated the viability of producing high-yield biodiesel from waste cooking oil (WCO) using a magnetic bifunctional calcium and iron oxide nanocatalyst derived from empty fruit bunches (EFB). The Eco-indicator-99 impact assessment, performed using OpenLCA, identified the transesterification phase as the primary hotspot, with fossil fuel resource depletion showing the highest impact at 39.029 Pt per 1000 kg of biodiesel. A sensitivity analysis revealed that solar power could reduce fossil fuel use, but panel production may lead to more harmful emissions than natural gas combustion. Utilizing WCO and nanocatalysts from EFB offers a sustainable alternative to the conventional methods.